Agricultura e sustentabilidade: Esforços brasileiros para mitigaç\~ao dos problemas climáticos - Nilo Luiz Saccaro; José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– The agricultural sector is central to achieving internationally agreed commitments in terms of mitigating the effects of climate change. Although future scenarios indicate the possibility of reducing areas suitable for various crops, for specific regions or for Brazil as a whole, it is possible both to develop new knowledge and technologies that allow sustainable production as well as to reduce the environmental impact of Brazilian agriculture. Thus, the objectives of this text are: i) to present briefly a review of the literature and the main results of regional impacts of climate change on Brazilian agriculture; ii) highlight public policies that can mitigate climate change problems; and iii) discuss how Brazilian agriculture can adapt to the impacts of climate change, mainly through the adoption of new technologies, including management. Productive integration, besides generating economies of scale and scope, can contribute to increase the system's efficiency, increasing production per unit of input. However, it should be emphasized that in order to foster integrated production, it will be needed to invest in the training and education of productive agents. Knowledge is the basis of transformation.
Keywords: Q01; 330; agriculture; productivity; climate change; environmental sustainability